The Effectiveness of the PQRST Strategy in Teaching Reading Skills at Al-Muddatsiriyah Islamic Senior High School Jakarta - Siti Aisyah; Mukhshon Nawawi; Azkia Muharom Albantani (Prodi Pendidikan Bahasa Arab, Universitas Muhammadiyah Tangerang, 2025)
This study aims to determine the effectiveness of using the PQRST strategy (Preview, Question, Read, Summarize, Test) in teaching reading skills. In addition, this research examines the steps for implementing this strategy, measures students' comprehension levels after its application, and demonstrates students' learning outcomes in Maharah Qira’ah using the PQRST strategy. This study employs a quantitative approach with a quasi-experimental method and a non-equivalent control group design. The sample consists of eleventh-grade students at Madrasah Aliyah Al-Muddatsiriyah, totaling 58 students. The researcher divided the students into two groups: 29 students in the experimental group and 29 students in the control group. Data collection involved pre-test and post-test assessments as well as interviews. For data analysis, the researcher conducted a normality test using the Kolmogorov-Smirnov test, a homogeneity test, and hypothesis testing using the t-test and N-Gain test through SPSS Statistics 27. The results of this study show that the average post-test score for the experimental group (82.58) is higher than that of the control group (64.89). Based on this difference, the researcher concludes that the average score of the experimental class is higher than that of the control class. Additionally, the independent sample t-test resulted in a value of 0.00 < 0.05, indicating that ??0 is rejected and ????? is accepted. The N-Gain test score shows that the use of the PQRST strategy achieved a score of 0.61 or 61%, which falls within the moderate effectiveness category. Therefore, based on statistical tests, the PQRST strategy is declared effective with a moderate level of effectiveness in teaching reading skills.Keywords: Effectiveness, PQRST Strategy, Maharah Qira’ah. مستخلص البحثيهد? هذا البحث إلى الكش? عن مدى ?عالية استخدام استراتيجية PQRST (الاستعراض، الأسئلة، القراءة، التلخيص، الاختبار) ?ي تعليم مهارة القراءة. والكش? عن كي?ية استخدامها وخطواتها، وقياس ?هم التلاميذ بعد تطبيق هذه الإستراتيجية ?ي تعلم اللغة العربية، وخاصة ?ي مهارة القراءة، وعن نتائج تعلم التلاميذ ?ي تعليم مهارة القراءة باستخدام استراتيجية .PQRST هذا البحث هو البحث الكمي باستخدام طريقة شبه التجريبي (Quasi Experiment) ومع تصميم المجموعات غير المتكا?ئة (Nonequivalent Control Group Design). والعينة ?ي هذا البحث من الص? الحادي عشر ?ي المدرسة الثانوية الإسلامية المدثرية، ومجموعهن 58 تلميذ. قسمت الباحثة التلاميذ إلى مجموعتين،29 تلميذ ?ي المجموعة التجريبية و29 تلميذ ?ي المجموعة الضابطة. لجمع البيانات استخدمت الباحثة على الاختبارين (اختبار القبلي والبعدي(، والمقابلة. و?ي تحليل البيانات قامت الباحثة باختبار التوزيع الطبيعي كوملوجورو? -سميرنو?Kolmogrov-Sminrov) )، واختبار التجانس واختبار ال?رضيات باستخدام اختبار Independent Sampel T- Test واختبار N-Gain باستخدام .SPSS Statistic 27 تثبت نتائج هذا البحث أن درجات الاختبار البعدي للمجموعة التجريبية حصلت على متوسط (82،58) مقارنة بالمجموعة الضابطة (64،89). وبناءً على هذا الاختلا? الدارجة ذكرت الباحثة إلى أن متوسط درجات المجموعة التجريبية كان أكبر من المجموعة الضابطة. إضا?ة إلى ذلك، علاوة على ذلك حصلت نتائج ت مستقل (Independent Sample T-Test) هي 0،00 < 0،05 ، بمعنى ال?رضية الص?رية ( (Ho مر?وضة وال?رضية البديلة H???)) مقبولة. أما بالنسبة لنتائج اختبار N-Gain ?قد أظهرت أن استخدام استراتيجية PQRST بقيمة 0،61 أو ما يعادل 61% ?ي مستوى متوسط. وبالتالي، تشير نتائج البحث بناءً على الاختبارات الإحصائية إلى أن استراتيجية PQRST ?عالة بمستوى متوسط ?ي تعليم مهارة القراءة. الكلمات الم?تاحية: ?عالية، استراتيجية PQRST، تعليم مهارة القراءة.